Evaluation of Ajuga bracteosa for antioxidant, anti-inflammatory, analgesic, antidepressant and anticoagulant activities. Issue 1 (December 2016) - Kayani, Waqas; Dilshad, Erum; Ahmed, Tanveer; Ismail, Hammad; Mirza, Bushra
Abstract Background Ajuga bracteosa has been extensively used traditionally for the treatment of a variety of diseases. The aim of the study was to scientifically validate the wide-scale exploitation ofA. bracteosa in folk medicine various in vitro and in vivo assays. Moreover, these activities were related to the intrinsic biologically active phytoecdysteroids ofA. bracteosa . Methods Aerial and root parts ofA. bracteosa were first extracted separately with chloroform (Ab CA andAb CR) and the residue was again extracted with methanol (Ab MA andAb MR). Total flavonoid and phenolic contents were assayed as quercetin (QE) and gallic acid equivalents (GAE), respectively. These extracts were analyzed for in vitro antioxidant assessment including DPPH and H2 O2 (% inhibition of free radicals), and reducing power and phosphomolybdenum methods (ascorbic acid equivalents AAE mg/g DW). Further, these extracts were assayed in vivo in separate groups of Sprague–Dawley rats for carrageenan induced rat paw edema inhibition, hotplate antinociception, forced swim antidepression and anticoagulation. Dose of each crude extract and standard drug given to rats was 200 mg/Kg- and 10 mg/10 mL/Kg body weight respectively. Plant extracts and standard drugs were administered orally, 60 min prior to the conduction of assays. Moreover, biologically active phytoecdysteroids were screened inA. bracteosa with the help of RP-HPLC. Results Ab MA represented highest values of flavonoids (QE 1.98 % DW) and phenolic contents (GAE 5.94 % DW), significantly scavenged DPPH radicles (IC50 36.9) and reduced ferric ions with 718.4 mg ascorbic acid equivalent/g (AAE). Highest total antioxidant capacity was expressed byAb MR (927 mg AAE) with an IC50 value 19.1 μg/mL. The extracts which were found potent anti-oxidants, were also good at in vivo activities.Ab MA significantly reduced edema in all the three hours of treatment (67.9, 70.3 and 74.3 %).Ab MA also showed maximum nociceptor suppression in analgesic assay by delaying the time to start licking of paws in rats (57.7 ± 4.9 s). In addition, maximum anti-coagulation was also exhibited byAb MA (89.3 s), while all extracts were found strong antidepressants (≤15.66 s immobility time). Screening of biologically active phytoecdysteroids revealed the presence of 20-hydroxyecdysone (20-HE), makisterone (MKA), cyasterone (CYP) and ajujalactone (AJL). Total phytoecdysteroid content found inA. bracteosa was 1232.5 μg/g DW and 20-HE was most abundant (1232.5 μg/g DW) as compared to other phytoecdysteroids. Conclusion Based on the tested in vitro and in vivo activities, Ab MA was found to be a promising bioactive extract. These activities can be attributed to the intrinsic polyphenols and phytoecdysteroids contents ofA. bracteosa .